Implementation Of Modelling Techniques Of Group Guidance Service to Develop the Student’s Attitudes - Setyawan, David Ari (IAIN Kudus, 2022)
In this counseling guidance has the aim to describe group guidance with modeling techniques in developing students' attitudes towards teachers. The method used in this paper is the successful application of modeling technique group guidance services to develop students' attitudes towards teachers, the application of modeling techniques using group guidance. The target or application of the modeling technique group guidance service is the students of . For guidance and counseling teachers, they should continue to explore counseling approaches and provide group guidance on modeling techniques in overcoming the attitude problems of students. Keywords: Group Guidance, Attitude Modelling Techniques